GUIDELINES FOR PREVENTING BOYS FROM ENTERING INTO PROSTITUTION IN THAILAND - Sukunya Buranadechachai,; Parinya Siriattakul, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This mixed, predominantly quantitative research aims to identify 1) the current status of boy prostitutes in Thailand; 2) steps leading boys into prostitution in Thailand;3) factors inducing boys to enter prostitution, and 4) guidelines for preventing boys from entering into prostitution. The research sample consisted of 140 male service workers between the ages of 15 and 20. Questionnaires were used to collect the data, which were subjected to a Path Analysis. The study found: 1) no male service workers were under 18 years of age, but a small number were under 20 years of age; 2) peer influence, chiefly through word of mouth, influenced the boys who entered prostitution; 3) work attitudes and sexual attitudes were also influences; and 4) close family relationships are key to preventing boys into prostitution. Preventing children from entering prostitution starts with the family. Parents need to care for their children with love and understanding. Broken family situations contribute to children running away from home, and subsequently forces them to support themselves by every possible means, both legal and illegal. Schools need to take more active roles in preventing children from entering into prostitution. They should foster in children a sense of human dignity, stressing how prostitution deprives sex workers of human value and human dignity Initiatives should also stress how buyers of sex services deprive sex workers of their human dignity and of better opportunities in life. The state itself should make the public aware of legal punishments applicable to those involved in buying and selling sex services, and of how the buying and selling of sex services is a shameless violation of human value and dignity.